KAJIAN SOSIAL YURIDIS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK Tika Andarasni Parwitasari - Tika Andarasni Parwitasari (STMIK Sinar Nusantara, 2016)
Globalization in all fields, including in this case is the globalization of information, bringing Indonesia as part of a world information society. Advancements in Information Technology has led to changes in the activities of human life in various fields, which directly has influenced the birth of the forms of new legal acts. Development of information and technology so rapidly requires the establishment of a regulation regarding the use and management of information technology in order to educate as well as the welfare of the nation. Law Number 11 of 2008 on Information and Electronic Transaction present as a legal regulation for the Indonesian people to continue to use and exploit information technology in order to maintain, preserve, and strengthen national unity, as well as providing legal certainty in the activities of electronic trade to support national economic growth. Keywords : Information Technology , Electronic Transactions .